Association of dementia diagnosis with urinary tract infection in the emergency department. Issue 6 (20th October 2020) - Yourman, Lindsey C.; Kent, Tyler J.; Israni, Juhi S.; Ko, Kelly J.; Lesser, Adriane
Abstract: Objectives: Overdiagnosis of urinary tract infections (UTI) among people living with dementia is a nationally recognized problem associated with morbidity from antibiotics as well as multidrug‐resistant bacteria. However, whether this problem also exists in the emergency department (ED) is currently unknown. Methods: To examine the association between dementia and UTI diagnosis in the ED we performed a retrospective analysis of Medicare beneficiaries older than 65 years old who presented to an ED in 2016. A diagnosis of UTI was present in 58, 580 beneficiaries, and 321, 479 beneficiaries without a diagnosis of UTI served as the comparison group. Our logistic regression model controlled for dementia, older age, female sex, Medicaid status, skilled nursing facility residence, history of prostate cancer, recent urinary catheter use, recurrent UTI, and multiple comorbidities. Results: In our model, people living with dementia had over twice the odds (odds ratio = 2.27, 95% confidence interval = 2.21, 2.33) of being diagnosed with a UTI in the ED compared to those without dementia despite their lower prevalence of symptoms and signs localizing to the genitourinary tract (3.8% vs 8.9%, respectively). Conclusion: This is the first study from a national database that examines the association of dementia with UTI diagnosis among older adults who visit the ED. Our study could not establish whether the UTI diagnoses in the ED were accurate but does imply a disproportionate burden of UTI diagnoses in people living with dementia despite their lower prevalence of clinical criterion. Antimicrobial stewardship in the ED should address the complexity of UTI diagnosis in dementia.